2019
DOI: 10.1038/s41598-019-52156-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of axial length and myopic macular degeneration to levels of molecular factors in the aqueous

Abstract: To elucidate the molecular processes associated with the development of myopic macular degeneration (MMD), we measured the intraocular concentrations of molecular factors in emmetropic and myopic eyes. This is a retrospective clinic-based case-control study that included eyes undergoing routine cataract surgery whereby aqueous humour samples were obtained. We measured the concentrations of pigment epithelium derived factor(PEDF), matrix metalloproteinase 2(MMP-2), tissue inhibitor of metalloproteinase(TIMP-2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“… 137 Alterations in the cytokine levels have also been described in eyes with pathologic myopia and may contribute to the pathogenesis of myopic MNV. 138 In eyes with myopic MNV, an increased VEGF level has been found in the aqueous humor compared with eyes undergoing cataract surgery. 139 There have also been a suggestion that genetic or hereditary factors may play a role in the development of myopic MNV.…”
Section: Clinical Aspects Of Pathologic Myopiamentioning
confidence: 99%
“… 137 Alterations in the cytokine levels have also been described in eyes with pathologic myopia and may contribute to the pathogenesis of myopic MNV. 138 In eyes with myopic MNV, an increased VEGF level has been found in the aqueous humor compared with eyes undergoing cataract surgery. 139 There have also been a suggestion that genetic or hereditary factors may play a role in the development of myopic MNV.…”
Section: Clinical Aspects Of Pathologic Myopiamentioning
confidence: 99%
“…This was done because posterior staphyloma causes posterior bulging of the eyeball and patients with myopic maculopathy can have reduced visual acuity (worse than 20/40); thus, these could have potentially been inferred in biometric evaluation. [ 25 ] An optical non-contact biometer (Lenstar LS 900, Haag-Streit, Switzerland) was used by a single ophthalmic technician for assessing the biometry of all eyes. Measurements that were recorded included AL (from the corneal epithelium to the internal limiting membrane of the retina), central corneal thickness (CCT; from the corneal epithelium to the endothelium), average Keratometry, anterior chamber depth (ACD; from corneal endothelium to the anterior capsule of the crystalline lens), lens thickness (LT; from the anterior capsule of the lens to the posterior capsule of the lens), and white to white diameter (WTW; the horizontal distance between nasal limbal border to the temporal limbal border).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Sharma et al’s 19 study showed a higher tear concentration of dopamine than in plasma samples in adults, indicating that tear dopamine assessments can be used to monitor dopamine levels. Cheung's 24 study showed the AREG concentrations in 61% of the aqueous samples were lower than the limit of detection (2.122 pg/ml). In the present study, the average AREG concentration in tear fluids was 110.60 ± 4.31 pg/ml (Table S4), and none of the measurements were below the limit of detection, suggesting a higher concentration of AREG in tears than in aqueous samples.…”
Section: Discussionmentioning
confidence: 96%